TWILIGHT: A Randomized Trial of Ticagrelor Monotherapy Versus Ticagrelor Plus Aspirin Beginning at 3 Months in High-risk Patients Undergoing Percutaneous Coronary Intervention - Johny Nicolas (Radcliffe Medical Media, 2020)
A P2Y12 inhibitor-based monotherapy after a short period of dual antiplatelet therapy is emerging as a plausible strategy to decrease bleeding events in high-risk patients receiving dual antiplatelet therapy after percutaneous coronary intervention. Ticagrelor With Aspirin or Alone in High-Risk Patients After Coronary Intervention (TWILIGHT), a randomized double-blind trial, tested this approach by dropping aspirin at 3 months and continuing with ticagrelor monotherapy for an additional 12 months. The study enrolled 9,006 patients, of whom 7,119 who tolerated 3 months of dual antiplatelet therapy were randomized after 3 months into two arms: ticagrelor plus placebo and ticagrelor plus aspirin. The primary endpoint of interest, Bleeding Academic Research Consortium type 2, 3, or 5 bleeding, occurred less frequently in the experimental arm (HR 0.56; 95% CI [0.45–0.68]; p<0.001), whereas the secondary endpoint of ischemic events was similar between the two arms (HR 0.99; 95% CI [0.78–1.25]). Transition from dual antiplatelet therapy consisting of ticagrelor plus aspirin to ticagrelor-based monotherapy in high-risk patients at 3 months after percutaneous coronary intervention resulted in a lower risk of bleeding events without an increase in risk of death, MI, or stroke.